-3=1+6x-7x

Simple and best practice solution for -3=1+6x-7x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3=1+6x-7x equation:


Simplifying
-3 = 1 + 6x + -7x

Combine like terms: 6x + -7x = -1x
-3 = 1 + -1x

Solving
-3 = 1 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
-3 + x = 1 + -1x + x

Combine like terms: -1x + x = 0
-3 + x = 1 + 0
-3 + x = 1

Add '3' to each side of the equation.
-3 + 3 + x = 1 + 3

Combine like terms: -3 + 3 = 0
0 + x = 1 + 3
x = 1 + 3

Combine like terms: 1 + 3 = 4
x = 4

Simplifying
x = 4

See similar equations:

| -19f+13=-12-20f+14 | | 2x^3-5x^2-8x+16=0 | | 20+7c=8c+4 | | 6-3x=-2x+-10 | | 5a-2=3a+11 | | 4x^2-9x-17=0 | | 26+17x=11x+23 | | 11r+19=1-12r+6 | | -14z=14-12z | | p-9=15-2p | | 3=x+6-1 | | 6h-10=10+10h | | 17(100)+22x=3086 | | -7t=-4t+9 | | 1=3-m | | f(x)=-2x^2+12x-14 | | -9-8n=8-5n+7 | | 0.5(x+1)+1=0.2 | | 2x+(-89)=110 | | (x^3/4*y^1/8*z^1/6) | | -94+41x+3x^2=0 | | x^15=3.5 | | 4x^8/16x^8 | | 3x/5=1/2 | | 4(r+3)=-16 | | x^2-20x+101=0 | | 10-4g=5g-8 | | -m+6=-2m | | 3+q=8 | | 8+7j=4j-10 | | q/185 | | 5x+2=-1+13 |

Equations solver categories